Evidence of unidentified «aeroplanes» in Viciebsk guberniya in 1914–1915: a look through the prism of the era - Butov, Ilya S. (Journal of the Belarusian State University. History, 2020)
The article is devoted to the Belarusian anti-aeroplane campaign of 1914–1915, i. e. to counteract the speculation that rapidly spread across the provinces about the appearance of enemy aeroplanes and airships behind the front line. Documents and materials from the National Historical Archive of Belarus, State Archive of Russian Federation and State Archive of Pskov Region funds concerning the verification of reports about aeroplanes in the Viciebsk guberniya are reviewed and analyzed. It is noted that the mass appearance of rumors about airplanes took place in the Viciebsk guberniya in several stages: at first, according to the descriptions of eyewitnesses, they were only a shapeless flying mass, and later information about them became more specific and even reports about their descent were checked. All this led to a serious problem – under the influence of panic, cases of superstitious soldiers firing at their own planes became more frequent, which could directly affect the course of military operations, in particular, the supply of advanced weapons and the latest intelligence. It is also important to consider the impact of the issue on the rear, which resulted primarily in the population fanning rumors directed against rich landowners, and the growth of social tension as a result. It is shown that the local anti-aeroplane campaign had a Baltic and Pskov «scurf», naturally complementing the actions of local authorities and the population. It is concluded that most of the reports from the Viciebsk guberniya and its borders, cited in the documents, do not describe observations of real combat or reconnaissance aircraft of the enemy, but only give an incorrect interpretation by eyewitnesses of any natural or astronomical phenomena as well as your own aeroplanes that occurred due to phobic images of new equipment in the eyes of the local population, reinforced by military hysteria and militaristic psychosis.